2014
DOI: 10.1111/petr.12398
|View full text |Cite
|
Sign up to set email alerts
|

The use of a Berlin Heart EXCOR LVAD in a child receiving chemotherapy for Castleman's disease

Abstract: We present the unique case of a pediatric patient who received chemotherapy for a diagnosis of CD, while mechanically supported with a Berlin EXCOR LVAD secondary to restrictive cardiomyopathy. A four-yr-old previously healthy male with restrictive cardiomyopathy required MCS after cardiac arrest but was diagnosed with multicentric CD, a non-malignant lymphoproliferative disorder fueled by excessive IL-6 production. Treatment with IL-6 blockade (tocilizumab) every two wk and methylprednisolone had no effect on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Since its implementation, long‐term survival rates for pediatric end‐stage heart failure have improved dramatically, and the EXCOR ® has emerged as a new standard of care for small children requiring mechanical support as a bridge to heart transplantation . Its success as a long‐term device option in pediatric heart failure patients with DCM has sparked interest in implementation of the EXCOR ® Pediatric VAD in other contexts of heart failure including CHD and single ventricle anatomy, as well as restrictive heart disease …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since its implementation, long‐term survival rates for pediatric end‐stage heart failure have improved dramatically, and the EXCOR ® has emerged as a new standard of care for small children requiring mechanical support as a bridge to heart transplantation . Its success as a long‐term device option in pediatric heart failure patients with DCM has sparked interest in implementation of the EXCOR ® Pediatric VAD in other contexts of heart failure including CHD and single ventricle anatomy, as well as restrictive heart disease …”
Section: Discussionmentioning
confidence: 99%
“…12,13 Its success as a long-term device option in pediatric heart failure patients with DCM has sparked interest in implementation of the EXCOR ® Pediatric VAD in other contexts of heart failure including CHD and single ventricle anatomy, as well as restrictive heart disease. [14][15][16][17][18] Historically, restrictive disease has been considered a risk factor for poor outcome with mechanical support. 3 In particular, this group of patients are thought to be at elevated risk of complications of VAD In this review, we found that 50% pediatric patients with diastolic dysfunction who were implanted with the EXCOR ® survived to heart transplant or recovery.…”
Section: Discussionmentioning
confidence: 99%
“…It is harder to support children with RCM with left ventricular assist devices (LVAD) due to smaller ventricular cavity sizes and because the right ventricle is usually affected as well. There are reports of successful bridging to cardiac transplantation with the Berlin EXCOR® LVAD [ 217 , 218 ]. All had left atrial cannulation and one patient required bi-ventricular devices.…”
Section: Restrictive Cardiomyopathymentioning
confidence: 99%
“…The literature specifically addressing the use of durable VAD support in children with HF and a recent history of cancer is limited to case reports 9–14 15 .…”
Section: Introductionmentioning
confidence: 99%
“…9,10 The literature specifically addressing the use of durable VAD support in children with HF and a recent history of cancer is limited to case reports. [9][10][11][12][13][14] There are no guidelines on how to proceed in pediatric patients who develop worsening HF after recently completing their cancer treatment, and the ISHLT advocates for individualized risk stratification for cancer recurrence in collaboration with oncologists. 15 In this manuscript, we review our single-center experience of durable VAD support for advanced HF in 6 children with chemotherapy-induced cardiomyopathy.…”
Section: Introductionmentioning
confidence: 99%